2011
DOI: 10.1111/j.1749-6632.2011.06088.x
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienols: inflammation and cancer

Abstract: Inflammation is an organism's response to environmental assaults. It can be classified as acute inflammation that leads to therapeutic recovery or chronic inflammation, which may lead to the development of cancer and other ailments. Genetic changes that occur within cancer cells themselves are responsible for many aspects of cancer development but are dependent on ancillary processes for tumor promotion and progression. Inflammation has long been associated with the development of cancer. The distinct characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 24 publications
3
31
0
Order By: Relevance
“…These observations are consistent with prior reports in which γ-tocotrienol has been found to be well tolerated in pre-clinical studies, with no reported toxicity [19, 41, 42]. …”
Section: Discussionsupporting
confidence: 92%
“…These observations are consistent with prior reports in which γ-tocotrienol has been found to be well tolerated in pre-clinical studies, with no reported toxicity [19, 41, 42]. …”
Section: Discussionsupporting
confidence: 92%
“…Chen et al reported that vitamin E supplementation could evidently inhibit or reverse the cytotoxic effects of cigarette smoke extract in a dose- and time-dependent manner in mouse embryonic lung cells [212]. A recent review by Nesaretnam and Meganathan linked tocotrienols and their roles in inflammation and cancer, and in this review, mechanism of the cellular signaling pathways of NF-κB, STAT3, and COX-2 were discussed [213]. In a meta-analysis and meta-regression study, although vitamin A, dietary vitamin E, and total vitamin E intake all reduced breast cancer risk significantly when data from all studies were pooled, the results became non-significant when data from cohort studies were pooled [214].…”
Section: Phytochemicals Used As Cancer Chemopreventive and Treatmementioning
confidence: 99%
“…Evidence has also accumulated demonstrating the more potent anticancer effects of TTs (δ and γ-TT in particular) compared with tocopherols in tumors1415. The mechanisms of the antiproliferative properties of tocotrienols are still under investigation and they seem to involve different intracellular pathways16171819.…”
mentioning
confidence: 99%